2020
DOI: 10.1016/j.heliyon.2020.e05090
|View full text |Cite
|
Sign up to set email alerts
|

Selected physical and chemical properties of soil under different agricultural land-use types in Ile-Ife, Nigeria

Abstract: This study examined changes in soil properties under different types of agricultural land-use. This was done with a view to extending knowledge on the nature of soil properties under long-term land-use practices. The study investigated six types of land-use: paddock, continuously cropped, secondary forest, teak, oil palm, and cacao plantations. Soil strength and saturated hydraulic conductivity were determined in-situ at two soil depths (0–15 and 15–30 cm) across the land-use types. Soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
8
7
0
1
Order By: Relevance
“…(2001) , who proved that phosphorus increases after establishing a silvopastoral arrangement with alder. These results were similar to those reported by Akinde et al. (2020) , who evaluated the phosphorus content for six types of agricultural land uses in Nigeria.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…(2001) , who proved that phosphorus increases after establishing a silvopastoral arrangement with alder. These results were similar to those reported by Akinde et al. (2020) , who evaluated the phosphorus content for six types of agricultural land uses in Nigeria.…”
Section: Resultssupporting
confidence: 90%
“…Alder in silvopastoral systems contributes to the improvement of phosphorus contents, as mentioned by Navia et al (2001), who proved that phosphorus increases after establishing a silvopastoral arrangement with alder. These results were similar to those reported by Akinde et al (2020), who evaluated the phosphorus content for six types of agricultural land uses in Nigeria. These results may also be due to the decrease in organic matter and organic phosphates, since the residues of leaves and decomposing material are found in the surface layer of the soil (Bailon, 2018).…”
Section: Available Phosphorussupporting
confidence: 90%
See 1 more Smart Citation
“…(2017) reported that conservation practices have the ability to increase soil fertility through increased SOC accumulation and can act as a mitigating mechanism to climate change. Previous study carried out in Nigeria ( Akinde et al., 2020 ) indicated that the establishment of conservative soil management practices such as manuring, mulching, and conservation tillage were suggested to prevent agricultural lands from degradation by improving SOC. Our results are in line with other studies performed under semi-arid conditions ( Sherrod et al., 2003 ; Engel et al., 2017 ; Sainju et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The region has a mean annual rainfall ranging between 800 mm and 1, 500 mm with about 85% of the rains falling from June to September. The average air temperature of the location is 24.7°C, and the type of soil is sandy loam ultisol (Salami and Sangoyomi, 2013;Oladele et al, 2019;Akinde et al, 2020). Besides, the initial physico-chemical properties of the experimental site were done in 2014 according to procedures cited in Oladele et al (2019;.…”
Section: Collection Procedures Of Materialsmentioning
confidence: 99%